Puppetry in theatre and arts education head, hands and heart - Smith, Johanna 1972- (London Methuen Drama, 2019)
"Puppetry in Theatre and Arts Education: Head, Hands and Heart is a textbook for students and teachers of theatre in education, schoolteachers, teaching artists outside of traditional school environments and puppetry enthusiasts, showing how puppetry can enliven classrooms, offering educational strategies and lesson plans to open out any syllabus and unlock new methods of learning. Author Johanna Smith provides fun and inexpensive interdisciplinary puppetry activities for educators and artists. Featuring exercises and essential advice, it places puppet manipulation, design and construction activities in the context of current research on the cognitive impact of arts education and the innovative concept of 'manual intelligence'. Puppetry in Theatre and Arts Education is a core text for theatre education courses as well as an essential addition to any teacher's arsenal of teaching strategies"--Provided by publisher.
Johanna's newspaper challenge -- What's a puppet? (the plastic bags lesson) -- Head, hands, and heart -- Everyday object puppets -- The power of design: puppet metaphors -- Dwarves word cards -- Chakabesh traps the sun: shadow puppets and storytelling -- The gingerbread kid: puppetizing children's literature -- Make a coral reef fish: puppetizing science -- Puppet filmmaking in the classroom -- Giant puppets and community celebrations: Johanna's version of the fabulous art of paper mache -- Quick and easy ideas for making puppets -- Finding material for puppetizing lessons -- A plan for devising a new puppet play.
Includes bibliographical references.
Keywords: Puppet theater in education